HARTA DALAM PERSPEKTIF ALQURAN: (STUDI TAFSIR AYAT-AYAT EKONOMI) - Batubara, Sarmiana (IAIN Batusangkar, 2018)
The paper deals with assets in the perspective of Alqur?an. It consists of the definition of assets, position of assets inAlquran, orders for seeking property, ownership in the views of Alquran, procedures for acquisition and distribution of assets inAlquran. The paper is in the form of literature studies that was conducted by reviewing related books, journals, magazines and articles. It was revealed several things, as the followings: 1) Assets are objects that can be owned, controlled, cultivated, and transferred, both tangible and intangible objects, both registered and unregistered objects, both movable and immovable objects and rights that have economic value; 2) Assets have a very important position in the Qur'an, as proven by the word mall in the Qur'an for 86 times in 79 quranic verses in 38 surah; 3) Orders to work or look for treasures are stated in Alqur?an, such as in surah At-taubah verse 105, Al-Mulk verse 15, Al-Ankabut verse 69, and Az-Zumar verse 39; 4) The absolute owner of the mallor everythingon this earth is Allah SWT, and human ownership is only relative. It means humans are only ones who have rights for managing and utilizing it as it is; 5) Obtaining mall can be done in various ways, including halal a'mal or ma'isyah. Then, the characteristics distribution of mall are fair and honest, because even in the smallest deeds we do, all will be accounted for in the hereafter.